Gallbladder neuroendocrine carcinoma: An important differential diagnosis of gallbladder adenocarcinoma. Issue 6 (10th May 2021) - Ikezawa, Kenji; Takada, Ryoji; Fukutake, Nobuyasu; Otsuka, Tomoyuki; Nagata, Shigenori; Ohkawa, Kazuyoshi
Abstract : Gallbladder neuroendocrine carcinomas (NECs) are a rare but important differential diagnosis of gallbladder cancer. This case report highlights the importance of pathological diagnosis and the efficiency of endoscopic ultrasound‐guided fine‐needle aspiration. Pathological diagnosis should be attempted because the treatment of gallbladder NEC differs from that of gallbladder adenocarcinoma, especially in unresectable cases.